Lingua franca? Polish-English communication problemsbased on the example of English terminology regarding adverse possession (Discourse of Law and Administration, 2024)
This article explores very important difficulty in Polish-English legal communication. The problem is connected to Polish-English and English-Polish law dictionaries. In order to show this the translations from such dictionaries of basic terms connected to regulation of adverse possession in England were analysed.
Keywords: adverse possession; Polish-English law dictionaries; English-Polish law dictionaries; legal communication